The ‘Italienprojekt’ of the Regesta Imperii in the Bicentenary of the Monumenta Germaniae Historica (Studi di storia medioevale e di diplomatica - Nuova Serie, 2019)
the paper presents the Italienprojekt, a joint research carried out by researchers from Regesta Imperii and Monumenta Germaniae Historica on imperial sources in Italian archives and libraries. It provides an historical excursus of the traditional cooperation between the two German projects concerning the archival campaigns in Italy and it describes strategy, preparatory works and the first results of the new project.
Keywords: Imperial sources; 14th-15th century; Monumenta Germaniae Historica; Regesta Imperii; Italy